PELAKSANAAN PENGELOLAAN SAMPAH DAN PARTISIPASI PEDAGANG UNTUK MENCIPTAKAN LINGKUNGAN BERSIH DI BASEMENT PASAR PETISAH KOTA MEDAN TAHUN 2012 - Nurul Fuady Daulay; wirsal hasan; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
The waste treatment and participation of the trader in build a clean environment in basement of Pasar Petisah (market) of Medan in 2012. Market is a big source of waste as by product of buying and selling activities that produce the waste that unusable, uncomforted and disposed and did not occurred by itself. This research aims to study the waste treatment and participation of the trader in build a clean environment in basement of Pasar Petisah (market) of Medan. This  research is a descriptive survey that conducted at basement of Pasar Petisah Medan in 2012 in which the data was collected through observation and interview using questionnaire to 64 respondents. The results of research indicates that of 64 respondents, there are 33 (51.6%) who have waste container and 31 respondent (48.4%) have not waste container. The waste treatment based on storage of waste indicators is classified into did not fulfill the health requirement category, the collecting of waste in fulfill the health requirement category, while transportation and waste treatment in fulfill the health requirement category. The participation of the trader in supply the waste container is classified into medium category (51.6%), disposal of waste in medium category (56.3%), the payment of waste retribution in good category (100%) and cleaning rule is in good category (93.8%). The waste treatment at basement of pasar petisah already fulfill the health requirement and still deficient the participation from respondents did dispose the waste in the available waste container. The management of market must enforce a rule about the market cleaning to enforce the trader did not dispose the waste in the front of their kiosk and provide them with sanction if violate the rule and it must to increase the participation of the traders by provide them with guide, direction and information about sanitation and waste treatment that fulfill the health requirement. Key words: Market, Waste Treatment, Participation of Traders